Trends of Patients' Characteristics Admitted Into a Multi-Professional Home Medical Care Service From 2000 to 2009 in Singapore. (February 2017) - Mittal, Rakhi; Young, M.E.; Tan, C. S.; Chen, C.; Tham, W. Y.; Seong, Lydia P. S.; Tan, T. L.; Koh, G. Choon-Huat
The main aim of this study is to present the socio-demographic, clinical, and functional characteristics of home medical care patients admitted into one of the oldest home care service over a 10-year period. Data were manually retrospectively extracted from the non-computerized medical records of all patients admitted into Code 4 Home Medical Service from January 1, 2000, to December 31, 2009. Records of 1, 069 patients were examined. Over the 10-year period, there was an increasing proportion of patients older than 70 years ( B [95% CI], 1.08 [0.43, 1.73]) and dependency on foreign domestic workers as primary caregivers ( B [95% CI], 4.65 [3.71, 5.58]). Cognitive impairment and functional dependency of the patients increased over the years, as assessed using Abbreviated Mental Test score < 7 ( B [95% CI], 1.73 [0.71-2.76]) and Barthel Index = 0 ( B [95% CI], 4.32 [2.74-5.91]). Knowledge about these trends may be helpful to project future demands for home medical care in Singapore.